1988
DOI: 10.1128/jb.170.5.2078-2082.1988
|View full text |Cite
|
Sign up to set email alerts
|

New function of vitamin B12: cobamide-dependent reduction of epoxyqueuosine to queuosine in tRNAs of Escherichia coli and Salmonella typhimurium

Abstract: Queuosine (Q), 7-(((4,5-cis-dihydroxy-2-cyclopentene-1-yl)-amino)methyl)-7-deazaguanosine, and Q derivatives usually replace guanosine in the anticodon of tRNAsGUN of eubacteria and of cytoplasmic and mitochondrial tRNAs of lower and higher eucaryotes except yeasts. Q appears to be synthesized de novo exclusively in eubacteria, and the free-base queuine serves as a nutrient factor for eucaryotes. Recently, a Q derivative, oQ, containing a 2,3-epoxy-4,5-dihydroxycyclopentane ring, has been identified in Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 29 publications
0
87
0
1
Order By: Relevance
“…Gene expression of the BtuB polypeptide has been shown to be repressed when cells are grown in the presence of cobalamin (24). Interestingly, it has also been shown that vitamin B12 is involved in the modification of tRNA (14). We therefore mieasured the trmA gene activity in cells grown in different cobalamin concentrations as described by Kadner (24).…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression of the BtuB polypeptide has been shown to be repressed when cells are grown in the presence of cobalamin (24). Interestingly, it has also been shown that vitamin B12 is involved in the modification of tRNA (14). We therefore mieasured the trmA gene activity in cells grown in different cobalamin concentrations as described by Kadner (24).…”
Section: Resultsmentioning
confidence: 99%
“…The purified tRNA transcript was analysed as described [6,10]. In short, the tRNA was hydrolysed with nuclease P1 (Boehringer Mannheim) and dephosphorylated with alkaline phosphatase from E. coli (Boehringer Mannheim).…”
Section: Reversed-phase Hplc Analysis Of Trna Nucleosidesmentioning
confidence: 99%
“…Although this modification at position 34 in the anticodon has been highly conserved in the course of evolution, only eubacteria can synthesize Q in tRNA de novo, involving unique S-adenosylmethionine and vitamin B 12 dependent reactions (4)(5)(6). Degradation of bacterial tRNAsQUN (Q-tRNAs) liberates the eukaryotic nutrition factor, queuine, the free base analogue of Q in tRNA (because queuine is present in eukaryotes as free base and as modified nucleoside in tRNA, we use the abbreviation 'q' or 'q-base' to denote the free base, and 'Q' for the modified nucleoside in tRNA).…”
Section: Introductionmentioning
confidence: 99%
“…The guanine acceptance is maximal when the tRNAs are completely Q-deficient (0% modification found in tRNA from HeLa cells grown in horse serum-supplemented medium), and is 0 when the tRNAs are completely converted to tRNAQUN (100% modification). (b) Cells were seeded as described under (a) and cultivated for 4 days with an exchange of the medium on the second day. Queuine alone (300 nM) or together with PDGF (final concentration 40 ng/ml; Biomol, Germany) and/or EGF (30 nM; Biomol, Germany) or with 12-O-tetradecanoylphorbol-13-acetate (TPA; 15 FM; Sigma, Germany) was added on day 4 without exchange of the medium and tRNA was isolated 24 h later.…”
Section: Introductionmentioning
confidence: 99%